If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 8 = 7y + 5 Reorder the terms: 8 + 25x = 7y + 5 Reorder the terms: 8 + 25x = 5 + 7y Solving 8 + 25x = 5 + 7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 25x = 5 + -8 + 7y Combine like terms: 8 + -8 = 0 0 + 25x = 5 + -8 + 7y 25x = 5 + -8 + 7y Combine like terms: 5 + -8 = -3 25x = -3 + 7y Divide each side by '25'. x = -0.12 + 0.28y Simplifying x = -0.12 + 0.28y
| -2(2x+1)+4=10 | | r+4=4-6r-7r | | -3x^2+9x=7 | | -(3c-4)=37 | | 6n+7=8n-13 | | F(20)=b | | 9x+2=25x+8 | | 6t+3t=6 | | 10x+3=7x-39 | | -2(x+11)=6 | | .25y+3=-5 | | 5x+1=-2-8 | | -2.89=1.7 | | 6y+3(5y-19)-(y+2)=-142 | | 10=3+2 | | 24=-6m | | 0.25+.20x+1=2.25 | | F(a)=20 | | 2(x+2)-3(2x+5)=5 | | 7d=14 | | 2+3(p+3)=21 | | 3x-2=44 | | 4g+4=2g+12 | | 4b^2-49g^2=0 | | x^3+7x^2-25x-150=x^2 | | .50x+.50x=x+1 | | (4x+2)-(12x+8)+10x-3=6+11 | | 8x-1=2x-37 | | 4=2(y-5)-2 | | .4x-9=-7 | | (2x-7)(4x+12)=0 | | 5T=2T-12 |